Comment on 'The detection rate of human papillomavirus in well‐differentiated squamous cell carcinoma and keratoacanthoma: is there new evidence for a viral pathogenesis of keratoacanthoma?'. (1st December 2019) - Taibjee, S.; Carr, R.; Craig, P.; Radonic, T.
Abstract: Linked Articles: Conforti et al. Br J Dermatol 2019; 181 :1309–1311 ; Conforti et al. Br J Dermatol 2019; 181 :1345–1346